Nanoscale Zero-Valent Iron Has Minimum Toxicological Risk on the Germination and Early Growth of Two Grass Species with Potential for Phytostabilization - Teodoro, Manuel; Clemente, Rafael; Ferrer-Bustins, Ermengol; Martínez-Fernández, Domingo; Pilar Bernal, Maria; Vítková, Martina; Vítek, Petr; Komárek, Michael (Nanomaterials (Basel, Switzerland), 2020)
Two Poaceae species, Agrostis capillaris and Festuca rubra, were selected for their potential as phytostabilizing plants in multicontaminated soils. These species are resistant to contamination and maintain high concentrations of contaminants at the root level. Nanoscale zero-valent iron (nZVI) is an engineered nanomaterial with the ability to stabilize metal(loid)s in soils; its potential toxicological effects in the selected species were studied in a germination test using: (i) control variant without soil; (ii) soil contaminated with Pb and Zn; and (iii) contaminated soil amended with 1% nZVI, as well as in an hydroponic experiment with the addition of nZVI 0, 25, 50 and 100 mg L-1. nZVI had no negative effects on seed germination or seedling growth, but was associated with an increase in shoot growth and reduction of the elongation inhibition rate (root-dependent) of F. rubra seedlings. However, applications of nZVI in the hydroponic solution had no effects on F. rubra but A. capillaris developed longer roots and more biomass. Increasing nZVI concentrations in the growing solution increased Mg and Fe uptake and reduced the Fe translocation factor. Our results indicate that nZVI has few toxic effects on the studied species.
Keywords: uptake; nano zerovalent iron; Agrostis capillaris; Festuca rubra; plant stress